Determinants of livestock waste-to-energy adoption among smallholder farmers in East Java, Indonesia - Evi Frimawaty; Fani Mardianti; Ravita Sari (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: Livestock waste holds significant potential as a renewable energy resource; however, waste management practices among smallholder farmers remain suboptimal. The adoption of waste-to-energy technology is limited, and the behavioral and socioeconomic determinants of this adoption gap are not yet fully understood. This study aims to identify livestock waste management practices, analyze differences in perceptions (energy-adopting and non-adopting farmers), and examine socioeconomic factors associated with biogas adoption. Methods: A quantitative cross-sectional survey was conducted in Sidoarjo Regency and Surabaya City, East Java Province, Indonesia. A total of 184 smallholder livestock farmers were selected through proportional random sampling. Data were analyzed using descriptive and comparative statistics, including Mann-Whitney U and Kruskal-Wallis tests to examine group differences in Theory of Planned Behavior (TPB) constructs. Findings: Non-energy practices dominate waste management, and the adoption of waste-to-energy technology remains limited. However, attitude scores, intentions, and behavioral control indicate a strong adoption potential. Mann-Whitney U test confirmed statistically significant differences for all four constructs: ATT (U = 180.5, p = .006), SN (U = 251.0, p = .026), PBC (U = 138.5, p = .002), and INT (U = 242.5, p = .022). Energy adopters consistently scored higher on all constructs, with the largest difference observed in PBC (Δ = +1.04). Fermentation plays a transitional behavioral role toward energy use and is comparable in behavioral readiness to biogas adopters. Conclusion: A tiered policy approach based on the adoption ladder is recommended to accelerate renewable energy uptake. Novelty/Originality of this article: Although various step-based adoption models have been suggested in the literature, the present study operationalizes the Adoption Ladder based on the constructs of TPB. Fermentation farmers can be considered at a behavioral stage of transition toward adopting biogas, based on empirically comparable attitudinal and intentional profiles relative to biogas adopters. The findings show that attitudes, subjective norms, and behavioral control affect adoption intentions, and fermentation farmers are positioned within a pre-adoption behavioral stage that indicates readiness for transition to biogas adoption.